Removal of Cd (II) from Aqueous Media by Adsorption onto Chemically and Thermally Treated Rice Husk - María Camila Hoyos-Sánchez; Angie Carolina Córdoba-Pacheco; Luis Fernando Rodríguez-Herrera; Ramiro Uribe-Kaffure (Journal of Chemistry)
Chemically and thermally treated rice husks were evaluated as a potential decontaminant of toxic Cd (II) in aqueous media. Rice husk (RH), a by-product from rice milling, was chemically treated with HCl and NaOH. Then, thermal treatments to 300, 500, and 700°C were applied. The chemical composition and morphological characteristics of RH were evaluated by different techniques. The specific surface area analysis of RH samples by BET nitrogen adsorption method provided specific surface areas ranging from 6 to 14 m2/g. SEM, FTIR, and EDX analyses of RH were carried out to determine the surface morphology, functional groups involved in metal binding mechanism, and C/O and C/Si ratios, respectively. The maximum Cd (II) adsorption capacity was 28.27 mg/g at an optimum pH, 6.0. The kinetic studies revealed that adsorption process followed the pseudo-second-order kinetic model.